Live or lecture capture: Evidence from a classroom random control trial. (June 2022) - Artz, Benjamin; Johnson, Marianne; Robson, Denise; Siemers, Sarinda
Abstract: This study employs a random control trial experimental design to compare student learning outcomes in situations with live lectures and situations with 'captured' – virtually recorded asynchronous – lectures. Students across five sections of introductory microeconomics were randomly assigned to attend a lecture in person or virtually. They were then quizzed on the material covered. Later in the semester, the same students were switched to the opposite modality and quizzed again on new material. An important feature of the experimental design was that the topics differed significantly in complexity. We find that with the more difficult topic, students watching recorded lectures performed better than those attending live lectures. For an easier topic, however, the opposite was true. Male students benefitted most from lecture capture, particularly on the more difficult topic. Women students were largely indifferent to changes in lecture modality.